Optimal injection solution for endoscopic submucosal dissection: A randomized controlled trial of Western solutions in a porcine model. Issue 3 (27th December 2017) - Mehta, Neal; Strong, Andrew T.; Franco, Matheus; Stevens, Tyler; Chahal, Prabhleen; Jang, Sunguk; Lopez, Rocio; Patil, Deepa; Abe, Seichiiro; Saito, Yutaka; Uraoka, Toshio; Vargo, John; et al.
Abstract : Background and Aim: When carrying out endoscopic submucosal dissection (ESD), procedural safety increases with greater tissue elevation and efficiency increases with longer‐lasting submucosal cushion. Fluids specifically developed for ESD in Asia are not commercially available in the West, leaving endoscopists to use a variety of injectable fluids off‐label. To determine the optimal fluid available in the West, we compared commonly used fluids for Western ESD. Methods: All phases were carried out in an ex vivo porcine stomach model. Phase 1 compared tissue elevation and duration of submucosal cushions produced by various standard volumes of various injectable solutions used for ESD. The two best‐performing solutions used off‐label were tested head‐to‐head in ESD in Phase 2. Phase 3 compared the best solution from Phase 2 to Eleview ®, currently the only submucosal injection fluid approved in the USA. In Phases 2 and 3, five ESD were carried out with each solution. The solutions were randomized and the endoscopist blinded to the solution. Results: The best‐performing solutions in Phase 1 were 0.4% hyaluronic acid, 6% hydroxyethyl starch (HES), and Eleview ® . Phase 2 compared 6% HES and hydroxypropyl methylcellulose (HPMC), showing that ESD with 6% HES was easier ( P  = 0.007), faster ( P  = 0.041) and required less injection volume ( P  = 0.003). In Phase 3, resection speed, ease of ESD and total volume per area resected were comparable between 6% HES and Eleview ® . Conclusions: Of the submucosal injection fluids currently available in the West, Eleview ® and 6% HES are the best‐performing solutions for ESD in a porcine model.